Fernando Savater. Coexisting the challenge facing the educational institution today - Morales Carrero, Jesús Alfredo (2022)
Claiming a dignified existence founded on reciprocal respect refers to a common principle that interweaves Savater's works, revealing his evident commitment to the regeneration of collective life with attachment to the common interest. His contributions make clear the commitment to the practice of a civic life, in which the human being reaches to develop personal virtues associated with honesty, active tolerance and overcoming individualism, as well as the adoption of inclusive attitudes in which equal and equitable treatment prevails as expressions of co-responsibility that seek to unite efforts of both hospitality and flexible reception of the differences and particularities that permeate the human race. This research, as a result of a documentary review, analyzes the contributions of Fernando Savater's works to the task of consolidating the global task that urges the educational institution to promote actions that superimpose dignifying coexistence within the framework of democracy, in which values such as empathetic understanding and fair and inclusive participation are erected as catalyzing elements of functional social bonds; This implies learning to coexist with the worldviews and multiplicity of belongings, assuming the vindication of the sense of uniqueness as well as the recognition of unity in diversity. In conclusion, living together in the educational institution depends on the establishment of common guidelines.